2000
DOI: 10.1002/1097-0150(2000)5:2<98::aid-igs4>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative tracking error analysis of five different optical tracking systems

Abstract: Both FlashPoint and Polaris have jitter less than 0.11 mm, although the error distributions differ significantly. Total jitter for all systems is dominated by the component measured in the axis directed away from the camera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 26 publications
(30 reference statements)
4
79
0
1
Order By: Relevance
“…We performed the reference motion path 20 times, taking care to keep the leg in neutral rotation via navigation. The accuracy of this system was within 1 mm for translational measurements and 1°for measurements of rotation [14,19].…”
Section: Methodsmentioning
confidence: 80%
“…We performed the reference motion path 20 times, taking care to keep the leg in neutral rotation via navigation. The accuracy of this system was within 1 mm for translational measurements and 1°for measurements of rotation [14,19].…”
Section: Methodsmentioning
confidence: 80%
“…Maurer , the tracking system's ability to accurately and consistently report the position of a tracked tool that will influence the accuracy throughout the IGNS intervention (Khadem, et al 2000), different tracked tools have different errors associated with their calibration and use , there are many different types of errors associated with relating the physical space of a patient with the space in which the preoperative images are taken through registration procedures (Zitova and Flusser 2003) (van den Elsen, Pol and Viergever 1993) (Fitzpatrick, West and Maurer Jr. 1998), and finally, a plethora of errors can be introduced by biological changes in the patient throughout the surgery (Hill, et al 1998). This section goes into some detail about some of these different types of errors and how they can affect IGNS interventions.…”
Section: Main Sources Of Errormentioning
confidence: 99%
“…For optical tracking systems, such as the Polaris infrared camera, one of these types of error is called "jitter", and refers to how the reported position of a static tool varies over time. The jitter varies with the type of tracking system used as well as the camera's position with respect to the dynamic reference frame (DRF) and the tracked tools (Khadem, et al 2000). This type of error is very important during the patient-to-image registration phase of an IGNS intervention.…”
Section: Tracking Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest advantages of an electromagnetic system, apart from the avoidance of radiation exposure, is that a visual connection between the navigation probe and sensor is not necessary. However, the electromagnetic tracking field is much smaller compared to that of optical systems, and also more delicate [24,25]. Maier-Hein et al [26] reported total puncture errors of 3.7 AE 2.3 mm (max.…”
Section: Improving Ct-guided Interventionsmentioning
confidence: 99%